DEVELOPMENT OF ANGIOSPERMAL ENCYCLOPEDIA IN THE JAVA TRADITION IN KALIWINING VILLAGE AS A SUPPORTING BOOK FOR JUNIOR HIGH SCHOOL STUDENTS - Lailatul Ulfa Magfiroh; Dinar Maftukh Fajar (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
This research aimed to describe the validity of the Angiosperm plant’s encyclopedia in the Javanese tradition of Kaliwining Village and to describe the students’ responses to the development of an encyclopedia of Angiosperm plants in the Javanese tradition of Kaliwining Villages. This research uses Research and Development (R&D) method with a 4D research model developed by Thiagarajan. In this research only 3 stages were carried out, there are Define, Design, and Develop. The subject consisted of validators, there are 2 expert lecturers, 1 science teacher, 6 students in the small-scale test, and 32 students in the large-scale test at SMPN 2 Rambipuji. The result of this research obtained an average percentage of validity tests, there are material experts of 90.91%, media experts of 97.65%, and science teachers of 90.91% with every valid category. Small-scale tests obtained an average percentage of 90.95%, which means that it can be used without revision, continued to large-scale tests the result of the average percentage is 85.98%, which means it is very suitable to be used as a supporting book.